Distribution System in an Islamic Economic Perspective - Adinugraha, Hendri Hermawan; Rahmawati, Ferida; Anas, Ahmad (SIL'AH: Jurnal Ekonomi Syariah, 2024)
This research aims to describe the distribution system from an Islamic economic perspective. The research method used in this study is library research. This research concludes that distribution in Islamic economics is based on fundamental human values, namely the value of freedom and justice. The purpose of distribution is twofold: first, wealth does not accumulate among a small group. Second, existing production factors must be fairly distributed for the country's prosperity. Islamic economics emphasizes the purification and cleansing of the human soul to create a prosperous life system without putting aside practical considerations. Islamic economics aims to achieve the goal of fair distribution of assets to society through education and experience. Islam requires equality among humans in terms of the struggle to obtain wealth without regard to differences in caste, creed, skin color, and so on. From an Islamic economic perspective, distribution aims to provide equal opportunities to everyone in economic struggle without distinguishing their social status. Islamic economics prevents the accumulation of wealth by controlling the growth and accumulation of wealth to be spent for the good of society.